Case Report: Endoscopic manifestations and clinical features of small intestinal lymphangioma—A report of two cases - Wang, Limei; Feng, Huang; Chen, Bingxin; Luan, Fujuan (Frontiers in Oncology, 2022)
Abstract: Objective: To analyze the clinical characteristics, auxiliary examinations, and treatment measures of small intestinal lymphangioma, to improve the clinical diagnostic ability of clinicians. Methods: This paper reports 2 cases of small intestinal lymphangioma in the Department of Gastroenterology, the First Affiliated Hospital of Soochow University, and makes a comprehensive analysis. Results: A 31-year-old female went to the hospital with complaints of dizziness, fatigue, and anemia. A 52-year-old woman complained of upper abdominal pain and went to the hospital with abdominal pain awaiting investigation. Two patients did three major routine examinations, tumor complete set, CT, capsule endoscopy, and deep enteroscopy, and all of them underwent complete resection of the affected intestinal segment. Pathology showed that both patients were small intestinal lymphangioma. Conclusions: The clinical manifestations of small intestinal lymphangioma lack specificity. Capsule endoscopy and deep enteroscopy are helpful for clinical diagnosis, and pathological examination is still the gold standard. Surgical treatment can achieve better results.